2022
DOI: 10.1126/sciadv.abj9406
|View full text |Cite
|
Sign up to set email alerts
|

An oomycete NLP cytolysin forms transient small pores in lipid membranes

Abstract: Microbial plant pathogens secrete a range of effector proteins that damage host plants and consequently constrain global food production. Necrosis and ethylene-inducing peptide 1–like proteins (NLPs) are produced by numerous phytopathogenic microbes that cause important crop diseases. Many NLPs are cytolytic, causing cell death and tissue necrosis by disrupting the plant plasma membrane. Here, we reveal the unique molecular mechanism underlying the membrane damage induced by the cytotoxic model NLP. This membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…In the example of wounding, release of amino acids likely occurs via the loss of membrane integrity that occurs during wounding and leakage of cell contents into the apoplastic space. However, in the case of touch or osmotic stress, how amino acids are rapidly released is less clear, but possibilities include that cellular stress responses involve the rapid activation of amino acid transporters, the exocytic release of amino acid containing vesicles as in neurotransmission in animals, or possibly by transient and nanoscale ruptures in the plasma membrane that allow leakage of cell contents ( 27 , 28 ). Having observed that living cells release amino acids that signal to neighboring cells ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the example of wounding, release of amino acids likely occurs via the loss of membrane integrity that occurs during wounding and leakage of cell contents into the apoplastic space. However, in the case of touch or osmotic stress, how amino acids are rapidly released is less clear, but possibilities include that cellular stress responses involve the rapid activation of amino acid transporters, the exocytic release of amino acid containing vesicles as in neurotransmission in animals, or possibly by transient and nanoscale ruptures in the plasma membrane that allow leakage of cell contents ( 27 , 28 ). Having observed that living cells release amino acids that signal to neighboring cells ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Candidate genes from six classes that have been characterised as virulence factors in other Phytophthora species ( Hua et al, 2013 ; Ma et al, 2015 ; Amaro et al, 2017 ; Chepsergon et al, 2020 ; Pirc et al, 2022 ) were selected for further investigation. These are genes encoding candidate cytoplasmic RXLR and CRN effectors, apoplastic effectors including elicitins, NLPs, CAZymes, and GPCRs involved in signaling ( Supplementary Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of their impacts on host plants, NLPs are classified into two forms: cytotoxic to eudicot and monocot plants and noncytotoxic [ 59 , 65 , 76 ]. Cytotoxic NLPs are expressed when a pathogen converts from biotrophy into necrotrophy and function as pore-forming toxins (PFTs), and these NLPs bind to the terminal monomeric hexose moieties of glycosyl inositol phosphoryl ceramide (GIPC) to cause cytolysis [ 65 , 76 , 77 , 78 ]. Noncytotoxic NLPs induce an immune response without cytolysis.…”
Section: Nlpsmentioning
confidence: 99%
“…As mentioned above, cytotoxic NLPs target and bind to the terminal hexose residues of glycosylinositol phosphorylceramide (GIPC) sphingolipids, which vary in total amount and concentration among different plants, which are located at the outer leaflet of the envelope membrane in plants [ 59 , 65 ]. The binding of GIPC-NLP is driven by electrostatic interactions, which can be strengthened in the presence of sterols and results in NLP conformational changes [ 65 , 77 , 86 ]. After binding, NLPs form functional oligomers and then form shallow transient pores that leak small molecules [ 77 , 87 ].…”
Section: Nlpsmentioning
confidence: 99%